Penyuluhan Kesehatan: Pengaruh Konsumsi Vitamin C Terhadap Peningkatan Kadar Hemoglobin Pada Remaja Putri Pondok Pesantren Tarbiyatul Banin Kaliwadas Cirebon - Supriyatin Supriyatin; Muhammad Ibnu Ubaidillah; Fiki Setiawan; Usdiyanto Usdiyanto; Ikhwani Ikhwani; Oktafirani Al Sas; Shinta Nur Asih (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2021)
Adolescents need iron intake and micronutrients that can help the absorption of iron, including vitamin C, therefore consuming vitamin C supplements that are water-soluble and widely distributed in food for the body plays a very important role in body health. The content of vitamin C is also found in vegetables, fruits and vitamin C supplements. The activity aimed to provide information about the significant effect on hemoglobin levels before and after consuming vitamin C in adolescent girls at the Tarbiyatul Banin Kaliwadas Cirebon Islamic Boarding School. Community service method by conducting observations, determining treatment targets and hemoglobin examinations. The results showed that there was a significant increase in hemoglobin levels before and after consuming vitamin C. The conclusion was that vitamin C could be used to help increase Hb levels in adolescent girls at the Tarbiyatul Banin Kalibadas Islamic Boarding School.